(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Around the world about millions of people using the medical devices or biomaterialsthat implanted in side human body in order to replace the function of unwell tissues ordamaged parts. In spite of the importance roles of these implants in saving or improvinghuman life, many of them are failed during short period or having complications. The mainfailure of the biomaterials caused by unqualified biocompatibility. Thus there are twomaterials types used for this field investment such as thin film nitinol and stainless steel.Stainless-Steel type 316L are widely used in biomaterial bone applications specially fixingdevices such as plates, screws, pins and artificial joints. On the other hands, thin film nitinolindicates a high possibility for applying in a small new vascular devices like heart valvesand covering stent grafts because of the singular beneficial properties of this material likesuper-elasticity and low-profile feature.